2020
DOI: 10.1007/s10494-020-00126-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Characterization of a Liquid Jet Injected into Air Crossflow with Acoustic Forcing

Abstract: This paper focus on the dynamic of a spray issued from the shearing of a liquid jet injected in an air crossflow submitted to high acoustic perturbations. Experimental and numerical approaches are used. Characterization of the liquid jet close to the injection location is obtained from high speed visualizations performed with a back lighting technique. Phase Doppler Anemometry gives useful information on the spray dynamics. The phase-averaged post processing method is chosen to describe the flow oscillations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Bodoc [19] found the periodic movement and breakup of a liquid column and the cyclic impact of a liquid jet on the upper wall of a channel and thus measured the time delays associated with each behavior. Desclaux et al [20] experimentally and numerically studied atomization in an oscillating gaseous crossflow. Their findings indicated that spray dynamics were influenced by both the oscillations of the liquid column and the crossflow, and the periodic flapping motion of the liquid column was induced by the acoustic fluctuating velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Bodoc [19] found the periodic movement and breakup of a liquid column and the cyclic impact of a liquid jet on the upper wall of a channel and thus measured the time delays associated with each behavior. Desclaux et al [20] experimentally and numerically studied atomization in an oscillating gaseous crossflow. Their findings indicated that spray dynamics were influenced by both the oscillations of the liquid column and the crossflow, and the periodic flapping motion of the liquid column was induced by the acoustic fluctuating velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, advanced technologies have been developed. In order to achieve fine and uniform fuel droplet distribution, manufacturers of combustion chambers developed lean-burning combustion regimes to minimize pollutant formation [4], numerous investigations of the atomization process in constant air flow have been published in the literature. It was demonstrated how different parameters, such as the moment flux ratio or the Weber number, affect the liquid behavior [5,6,7].…”
mentioning
confidence: 99%